Exploring the Application of the Caritas Coach Role in Nursing Practice. - Anderson, Jan Marie (International Journal for Human Caring, 2023)
This hermeneutic phenomenological study explored the lived experience of the Watson Caring Science Institute Caritas Coach Education Program graduates. Caritas coaches were interviewed to explore: how caring science influenced the development and implementation of the role, how graduates were affected as they lived out this role, and how caritas coaching affected the quality of nursing care. Three themes were identified: finding voice, living life with purpose and meaning, and the need for change in healthcare. Participant experience supported the importance of caritas coaching and its potential to change how nursing is practiced. It also offered an expanded view of nurse coaching.